A leadership looking glass: How reflected appraisals of leadership shape individuals' own perceived prototypicality and group identification. Issue 1 (2nd January 2023) - Begeny, Christopher T.; Huo, Yuen J.; Ryan, Michelle K.
ABSTRACT: Research on social identity and leadership rarely examines leadership processes from the perspective of leaders themselves. Three studies (experimental, longitudinal, cross-sectional) help fill this gap. Integrating social identity principles with a reflected appraisals perspective, we demonstrate that as individuals come to see themselves as (informal) leaders in a group, it positively affects their own sense of fit to the group prototype. Their own perceived prototypicality, in turn, yields a strengthened attachment to the group (identification). Importantly, we demonstrate this in racial and ethnic minority groups – an understudied context, yet where individuals develop meaningful conceptions of leadership and identification, with implications for their health and commitment to collective action. Altogether, this provides insights on social identity processes, and minority group leadership.